ENTERPRISE ARCHITECTURE PLANNING USING TOGAF (CV CASE STUDY. ZANANA INDONESIA) - Fikri Akbar Falcata Winata; Irfan Nurihsan; Siti Khotijah (Journal of Multimedia Technology and Applied Software, 2024)
Zanana Indonesia is a company engaged in Fast Moving Consumer Good (FMCG) where the main activity of this company is producing banana snacks. On CV. Zanana Indonesia is not yet fully aware of the important role of IT to support the business as a whole, the company also does not have a special unit that handles IT. therefore, the utilization of IT in the company has not been well planned. The use of IT and SI has not been comprehensive and centralized, utilization is only limited to the use of standard applications built into operating systems such as Microsoft Office to support the company's operational activities. Enterprise Architecture planning is expected to educate companies about the importance of the role of IT to support operational activities to be more effective and efficient and there is harmony between business and IT development to optimize the use of information systems and information technology. The basis for choosing TOGAF in Enterprise Architecture planning is because TOGAF provides a detailed overview of methods for building, managing, and implementing frameworks and information systems to be used as recommendations in development. From the results of the Enterprise Architecture planning that has been made, 4 pieces of new business process development have been combined with IT. For data architecture, 1 piece of new data structure design is obtained. For the application architecture, 4 new applications were obtained. Technology architecture results in hardware planning to support the new Enterprise Architecture. Then there are opportunities and solutions that companies will get if they implement EAs and there is also migration planning if EAs will be implemented in the company